Dragon fruit jelly: exploring the potential of peel in post-harvest loss reduction - Soares Magalhães, Deniete; Aparecida Salles Pio, Leila; de Barros Vilas Boas, Eduardo Valério; Costa Baratti, Ana Claudia; Pasqual, Moacir; Rangel Junior, Ivan Marcos (Revista Ceres, 2025)
The aim of this work was to evaluate the potential use of the peel of pitaya fruits for jam production. Four pitaya jelly formulations with different peel proportions used in place of the pulp (0, 20, 40 and 60%) were evaluated. The inclusion of peel in the formulation of red pitaya jelly is viable, and the product quality is maintained, especially at a 20% peel proportion, which is better accepted by tasters than are higher proportions. The 20% substitution of pulp with peel resulted in higher mean consistency and overall impression values than the other formulations. The levels of soluble solids and titratable acidity and the soluble solids/titratable acidity ratio did not significantly differ among the products, with mean values of 64.6%, 1.05%, and 61.67% with 20%, 40% and 60% peel addition, respectively. Substituting pulp with pitaya mesocarp resulted in an increase in jelly pH. The adhesiveness and cohesiveness of the jellies increased as the percentage of peel increased. The microbiological results of this study indicate the absence of microorganisms in the jellies. Thus, the use of peel in jam production can minimize production losses while adding value to the product and reducing waste disposal in the environment.